Brewers' spent grain (BSG)-based green dielectric materials for low-voltage operating solution-processed organic field-effect transistors. Issue 40 (27th September 2022) - Yun, Seungjae; Kim, Youngseok; Lee, Seunghan; Ho, Dongil; Kim, Jaeseung; Kim, Hyunjung; Marconi, Ombretta; Marrocchi, Assunta; Kim, Choongik
Abstract : A brewers' spent grain (BSG) based dielectric material was used in organic field-effect transistors (OFETs). The fabricated devices showed a maximum hole mobility of 2.30 cm 2 V −1 s −1 . Abstract : In this work, low-voltage solution-processed organic field-effect transistors (OFETs) utilizing biocompatible brewers' spent grain (BSG), a major by-product of the brewing industry, as the gate dielectric are reported. Specifically, arabinoxylan (AX) and mixed linkage (1-3, 1-4)-beta-d -glucan (BG), two most abundant polysaccharides in BSG, were employed and exhibited decent dielectric properties. To ensure good insulating properties, sol–gel-derived alumina was used with BSG (AX or BG) to fabricate hybrid organic/inorganic dielectrics, resulting in a high areal capacitance of ∼90 nF cm −2 . Green solvents instead of conventional toxic solvents were used in forming dielectric and semiconducting films for the fabrication of OFETs and the resulting devices based on 2-decyl-7-phenyl[1]benzothieno[3, 2- b ][1]benzothiophene (Ph-BTBT-C10 ) with BSG/alumina hybrid bilayer dielectrics exhibited the maximum hole mobility of 2.30 cm 2 V −1 s −1 at an operating voltage of <5 V.